Implementation of the Independent Curriculum in Improving the Quality of Education in SMA Negri 1 Belitang III - Pinky Permatasari; Khoirul Aldi; Anggun Nidiatika; Gergely Maja (Yayasan Adra Karima Hubbi, 2023)
The curriculum is the